2017
DOI: 10.17584/rcch.2017v11i1.5662
|View full text |Cite
|
Sign up to set email alerts
|

Efecto citotóxico del hipoclorito de sodio (NaClO), en células ápicales de raíces de cebolla (<i>Allium cepa</i> L.)

Abstract: El hipoclorito de sodio (NaClO), es un compuesto químico altamente tóxico y ampliamente utilizado por sus propiedades desinfectantes. Una de las especies vegetales más usadas para la detección de diferentes tipos de cambios genéticos causados por substancias químicas es Allium cepa L. mediante la cual se hacen pruebas para la vigilancia del medio ambiente. El objetivo de esta investigación fue evaluar el efecto citotóxico del hipoclorito de sodio (NaClO) en células apicales de raíces de cebolla (Allium cepa L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
3
5
1
Order By: Relevance
“…These results differ from those reported by Causil et al (2017), who in their test of sodium hypochlorite cytotoxic effect (NaClO), on apical cells of onion roots (A. cepa) they did not report significant differences in root growth for any of the evaluated concentrations. Likewise, these also contrast with the results obtained by Manrique et al (2011) where only inhibition percentages of 45% were reported in higher concentrations of 5 mg L −1 of sodium hypochlorite in onion roots.…”
Section: Root Growthcontrasting
confidence: 99%
See 3 more Smart Citations
“…These results differ from those reported by Causil et al (2017), who in their test of sodium hypochlorite cytotoxic effect (NaClO), on apical cells of onion roots (A. cepa) they did not report significant differences in root growth for any of the evaluated concentrations. Likewise, these also contrast with the results obtained by Manrique et al (2011) where only inhibition percentages of 45% were reported in higher concentrations of 5 mg L −1 of sodium hypochlorite in onion roots.…”
Section: Root Growthcontrasting
confidence: 99%
“…Mitosis tests were performed at 72 h, the root tips were cut 3-5 mm approximately, and immersed in hydrochloric acid for 15 min to break the cell walls (Causil et al, 2017). The staining was performed with Acetate-Orcein for 24 h. Once stained, the roots were arranged on slides and covered with a coverslip, where the squash technique was performed; with the yolk of the thumb a uniform pressure was exerted so that the cells dispersed and made visible each of the cellular phases (Valladolid et al, 2014).…”
Section: Microscopic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…After a period of seed growth (after 72 h), root tips of approximately 5-mm size of L. culinaris and P. sativum were rinsed with tap water and stained for 10 min with the compound aceto-orcein (Causil et al 2017 ). For the staining protocol, 6 slides were prepared for each treatment, and 1000 cells per 5 replicates were analyzed; pressure was exerted with a coverslip to make each cell phase visible by scattering the cells (Fiskesjö 1985; Salazar et al 2019 ; Salazar and Maldonado Bayona 2020 ).…”
Section: Methodsmentioning
confidence: 99%